1964
DOI: 10.3733/hilg.v35n09p185
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory study of three strains of codling moth,Carpocapsa pomonella(Linnaeus), exhibiting tolerance to DDT in the field

Abstract: Three field strains of DDT-resistant codling moths from differ ent areas in northern California were mass reared in the laboratory. The degree of DDT resistance in both larvae and adults was deter mined by using two methods of exposure to the insecticides. Topical applications (LD 50 ) were made to the moths, and the cage technique (LC 50 ) was used for the larvae. A DDT-susceptible labora tory strain of codling moth was used as the standard for comparison.The tests showed that all three of the field strains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1966
1966
1986
1986

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…(Bailey & Madsen, 1964;Riedl, unpublished). Similar data have been reported in Australia (Table IV), where probably the most extensive selection study was done by Rose & Hooper (1969) who subjected populations to azinphosmethyl for 10 years and found no evidence of resistance in any of the populations tested'.…”
Section: Susceptibility Values (Ld:o) For Strains Of the Codling Mothmentioning
confidence: 96%
See 1 more Smart Citation
“…(Bailey & Madsen, 1964;Riedl, unpublished). Similar data have been reported in Australia (Table IV), where probably the most extensive selection study was done by Rose & Hooper (1969) who subjected populations to azinphosmethyl for 10 years and found no evidence of resistance in any of the populations tested'.…”
Section: Susceptibility Values (Ld:o) For Strains Of the Codling Mothmentioning
confidence: 96%
“…Thereafter, a number of published and unpublished tests have been conducted on strains of adult moths from the western and midwestern areas of North America without finding evidence of a significant change in the susceptibilities of populations America andAustralia (1959--1980) Riedl, unpublished (I.14 9 (1978Riedl, unpublished (I.14 9 ( ---1980) DFFS (Santa Clara Co.) California 0.19 d 0.21 9 * Values for mixed sexes of adults unless indicated otherwise. (Bailey & Madsen, 1964;Riedl, unpublished). Similar data have been reported in Australia (Table IV), where probably the most extensive selection study was done by Rose & Hooper (1969) who subjected populations to azinphosmethyl for 10 years and found no evidence of resistance in any of the populations tested'.…”
Section: Uses Of Resistant Predatory Mites and Insects In Imp Systemsmentioning
confidence: 96%
“…These authors suggested that a dosage of 2 pg DDT per moth could be used as a discriminating dosage for the detection of DDT-resistance. The data of Bailey and Madsen (1964) for the same susceptible strain as used by Barnes and Moffitt (1963) show that 2 pg DDT per moth killed all susceptible individuals and Morris and van Baer (1959) also recommended 2 pg DDT per moth as a discriminating dosage.…”
Section: Continuous Exposure Testsmentioning
confidence: 99%
“…1968b). It is believed that the continuous-exposure test described in this paper provides "a convenient and practical way of monitoring for resistance" (Anon. 1968b) in C. pomonella and that the method warrants evaluation by other investigators.…”
Section: Continuous Exposure Testsmentioning
confidence: 99%
See 1 more Smart Citation